The Analysis of Coral Reef Coverage Condition in The Waters of Central Bangka Regency - Sudirman Adibrata; Wahyu Adi; Fera Angelia; Umam Komarullah; Dedi; Arham Hafidh Akbar; Eka Maulana; Sapriyadi; Sofyan; Dia Aldia; Animah; Citra Ayu; Robi Gunawan; Muhammad Mahatir; Sandri; Rizki Evitulistiono; Febrianto; Muhammad Ichsan Efendi; Agung Susanto; Muhammad Faris Alqodri; Nico Adriyansyah; Adisti Hafizah; Jemi Ferizal; Oka Arizona (Coastal and Marine Journal, 2023)
This research aims to discover the percentage of coral reef coverage and the condition of the coral reef ecosystem in small islands in Central Bangka regency waters. The research was conducted on May 2022 on six small islands: Panjang Island, Semujur Island, Ketawai Island, Ketugas Island, Gusung Asam Island, and Bebuar Island. The method used was underwater photo transect (UPT) and then analyzed using Coral Point Count with Excel extension software (CPCe). The result shows that of 6 small islands, only Semujur Island is populated. Coral reefs in small islands in Central Bangka regency were a type of fringing reef dan patch reefs with 3,0 - 8,8 meter depth. Standard damage criteria show that the damage was Moderate (44,60%) to Excellent (87,00%). The details were Moderate category on Ketugar Island, Good category was in Panjang Island, Gusung Asam Island, and Bebuar Island, while the coral reefs in Excellent category were in Semujur Island and Ketawai Island. 24 lifeform types were found with a dominant percentage value of approximately 18,47 - 46,87%. Lifeform was dominated by Coral Foliose (CF), Acropora Tabulate (ACT), dan Dead Coral with algae (DCA). Live coral reefs closer were dominated by healthy lifeforms, with most of the close being Dead Coral with algae. It showed that coral reefs might get disturbed by algae occurrence and triggers massive algae expansion. Fish in Coral reefs primarily targeted fish. It prefers the lifeform type to dead coral with algae lifeform.